Unique ECG Findings in Acute Pulmonary Embolism: STE with Reciprocal Changes and Pathologic Q Wave - Amanda Grant-Orser; Brennan Ballantyne; Wael Haddara (Case Reports in Critical Care)
A 68-year-old male presented to the emergency department with retrosternal chest pain, presyncope, and then a pulseless electrical activity cardiac arrest. An ECG prior to his arrest revealed ST elevations in leads V1–V3, Q waves in lead V2, and reciprocal ST depressions in the lateral and inferior leads. He received thrombolytic therapy for a presumptive diagnosis of ST elevation myocardial infarction. Return of spontaneous circulation was achieved and he underwent a coronary angiogram. No critical disease was found and his left ventriculogram showed normal contraction. His ongoing metabolic acidosis and dependence on an intra-aortic balloon pump, despite adequate cardiac output, prompted a CT pulmonary angiogram which showed multiple segmental filling defects. He was treated for a pulmonary embolism and was discharged 5 days later. Acute pulmonary embolism (APE) has variable clinical presentations. To our knowledge, this is the first case report of an APE presenting with these ECG findings suggestive of myocardial ischemia. In this case report, we discuss the underlying physiological mechanisms responsible and offer management suggestions for emergency department and critical care physicians to better expedite the treatment of APE mimicking acute coronary syndrome on ECG.